Village Fund Management Based On Permendagri Number 20 2018 - Hizkia Yesaya Kaloh; Nouke Sysca Oroh; Ika Prayanthi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to determine the level of adjustment between Permendagri No. 20 of 2018 and field findings at each stage of Village Fund management in one of the developing villages in North Sulawesi. Those stages are planning, implementation, administration, reporting, and accountability stages. The method used in this study is a descriptive method with a qualitative and quantitative approach using the village of XYZ as the object of research. The data in this study are divided into two, namely primary data and secondary data obtained through interviews with parties related to village funds such as the Village Head, Village Secretary, Treasurer, and Community. The research instrument is using a mobile phone that is used to record audio, video, and take pictures during data collection. The results of this study show the level of adjustment when compared between the rules and findings directly in the field, at the planning stage it is 69 percent, then at the implementation stages the adjustment rate is 75 percent, then the administrative stage gets 100 percent the adjustment rate, 50 percent the appropriate level at this stage. reporting and the final stage of accountability with an adjustment rate of 67 percent.